Giant calmaries Аrchiteuthis in the Southern ocean - Yukhov, V. L. (Ukrainian Antarctic Journal, 2014)
Abstract. There were investigated calamaries Architeuthis – objects of meal for the sperm whales in the Southern ocean expansion, some peculiarities of biology. The most often these calamaries are in the zone of 20–45° of the southern latitude. The Southern border is near 48° of the southern latitude. All cases of its detection are within the temperatures of surface waters 10–25°C, with the maximum at 17–20°C. Adults inhabit mesopelagic zone (200–700 m) and bathypelagic zone (700–1500 m), do not form concentration. Maximum general length of calamary – 1180 cm, weight – 260 kg. Maximum length of mantel is 250 cm, weight of eggs from ovaries is up to 6,5 kg. Main food is fish, calamaries.